Enhancing Inventory Accuracy and Operational Performance with ERP - Sudarmi, Elisabeth; Sunaryo, Widodo (Yayasan Sinergi Kawula Muda, 2024)
This narrative review explores the role of Enterprise Resource Planning (ERP) systems in enhancing inventory management across industries. Drawing from empirical studies, theoretical reviews, and case applications over the past 15 years, it highlights how ERP systems improve operational efficiency, inventory accuracy, and supply chain responsiveness. Key benefits include real-time data access, reduced manual errors, automation, and integration, with technologies like IoT and machine learning further supporting decision-making and coordination. Despite these advantages, challenges such as high costs, resistance to change, data quality issues, and skill gaps hinder implementation. The review emphasizes the need for integrated planning, user training, and strong data governance, and calls for more interdisciplinary research to address behavioral and contextual influences on ERP success. ERP is ultimately seen as a vital tool for navigating modern supply chain complexities.